Development of Low- Fat Firin Sutlac Pudding with Yellow Pumpkin for The Elderly with Heart Disease - Lestari, Lara Ayu; Lirizka, Sessy Paramita; Nurhayati, Aftulesi; Alamsyah, Putri Rahmah; Handoko, Matthew Nathaniel (Universitas Muhammadiyah Semarang, 2025)
Malnutrition is an important prognostic factor in elderly patients with coronary heart disease (CHD). Puddings can support nutritional intake in elderly patients with CHD. This study aims to develop a special dietary food product Firin Sutlac Pumpkin, a low-fat pudding. This study uses a complete random design with three formulas that combine yellow pumpkin and rice with different ratios, namely S1 (60:40), S2 (50:50), and S3 (40:60). The samples obtained were analyzed by organoleptic tests (hedonic test and hedonic quality). This study showed that increasing yellow pumpkin puree affected panelists’ preference for color, aroma, texture, and taste attributes. The estimated nutritional content of fiber also increased according to the increment of yellow pumpkin puree usage. The most optimal formula is 60% yellow pumpkin puree pudding (S3). S3 Firin Sutlac pudding contains 99.08 kcal of energy, 4.5 g of protein, 2.89 g of fat, 17.17 g of carbohydrates, and 0.89 g of fiber. A 100 g serving of S3 pudding contributes to 5.21-6.39% of the energy requirement for elderly aged 65-80 years and is eligible to be claimed as a low-fat food product.